2021
DOI: 10.4239/wjd.v12.i11.1942
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean diet and advanced glycation endproducts in patients with diabetes

Abstract: BACKGROUND In recent years, American Diabetes Association started to strongly advocate the Mediterranean diet (MD) over other diets in patients with diabetes mellitus (DM) because of its beneficial effects on glycemic control and cardiovascular (CV) risk factors. Tissue levels of advanced glycation endproducts (AGEs) emerged as an indicator of CV risk in DM. Skin biopsy being invasive, the use of AGE Reader has been shown to reflect tissue AGEs reliably. AIM To examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Through the multiligand receptor for advanced glycation end products (RAGE) on the vascular cells, AGEs play a key role in the inflammatory process [ 13 ]. It is well established that higher levels of AGEs are linked to diseases such as diabetes, chronic kidney disease, nonalcoholic fatty liver disease, obesity and cardiovascular diseases [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the multiligand receptor for advanced glycation end products (RAGE) on the vascular cells, AGEs play a key role in the inflammatory process [ 13 ]. It is well established that higher levels of AGEs are linked to diseases such as diabetes, chronic kidney disease, nonalcoholic fatty liver disease, obesity and cardiovascular diseases [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high consumption of olive oil, vegetables, fruits, unprocessed cereals, nuts, legumes, fish, and other seafood, moderate consumption of old cheese and red wine, and limited consumption of dairy products and meat are its principal characteristics. Apart from demonstrating benefit in many chronic diseases, a MD’s effects on individuals with obesity is well established, particularly in regard to the gut microbiota composition and the metabolome [ 102 , 103 , 104 ]. Moreover, since a substantial number of RCTs concerning the interrelation between a MD and gut microbiota were performed (unlike with other dietary interventions), inferences about this dietary regime are perhaps the most reliable ones.…”
Section: Effect Of Nutritional Interventions On Gut Microbiota and Me...mentioning
confidence: 99%
“…Similar results were obtained in another meta-analysis that also studied the relationship between a posteriori dietary patterns and MetS: a healthy/prudent diet was associated with a lower prevalence of MetS, while an unhealthy/Western pattern was associated with an increased risk of developing MetS [ 64 ]. Another popular dietary pattern, the Mediterranean diet, has also shown benefits regarding MetS [ 65 , 66 ]. In a meta-analysis by Kastorini et al, the combined effect of prospective studies and clinical trials showed that the Mediterranean diet is associated with a reduced risk of MetS (log hazard ratio: −0.69, 95% confidence interval (CI): −1.24 to −1.16) [ 67 ].…”
Section: Effects Of Diet On Metabolic Syndromementioning
confidence: 99%